EVALUASI PENGARUH INTERNET FINANCIAL REPORTING DAN KUALITAS LABA TERHADAP REAKSI PASAR MELALUI KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Sari, Ratna Dewi; Agus Munandar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study is to analyze whether or not there is a relationship between IFR (Internet Financial Reporting) which is proxied with the Internet Financial Reporting Index (IFRI), earnings quality by measuring earnings persistence to market reaction by measuring price earnings ratio (PER) and financial performance which is proxied by fixed asset turnover as an intervening variable. The type of research carried out is explanatory causal in quantitative methods using secondary data. The populations of data taken in this study were 14 companies indexed in the JII (Jakarta Islamic Index) with a time span of 2017-2020 so a total of 56 financial report data. The results showed that IFR and earnings quality had no effect on financial performance, IFR had an effect on market reaction, financial performance had a negative effect on market reaction and earnings quality had no effect on market reaction. IFR, earnings quality, and financial performance have a simultaneous effect on market reaction. Financial performance is an intervening variable in seeing the relationship between IFR and earnings quality with market reaction